An Extension of the Perseverative Cognition Hypothesis to Posttraumatic Stress Disorder Symptomatology: Cardiovascular Recovery in Relation to Posttraumatic Stress Disorder Severity and Cognitive Appraisals of Stress. Issue 1 (1st February 2018) - Kibler, Jeffrey L.
Abstract: Beyond the construct of cardiovascular reactivity, the measurement of cardiovascular recovery from stress represents an important index of exaggerated physiological arousal and disease risk. Cardiovascular recovery in posttraumatic stress disorder (PTSD) has not received adequate attention. The present study examined whether cardiovascular recovery following an oral speaking stressor was associated with the severity of PTSD symptoms, and whether cognitive stress appraisals of threat and challenge were significantly associated with PTSD severity and recovery. The sample consisted of 50 trauma‐exposed civilian women ranging from 19 to 49 years of age ( M = 30.9, SD = 7.8). The PTSD severity indices were quantified based on structured interview. Cardiovascular recovery was assessed at two posttask time points as percentage return to baseline; the recovery measures consisted of impedance cardiography‐derived cardiac output (CO) and total peripheral resistance (TPR), heart rate and blood pressure. Total PTSD severity was associated with less CO recovery, r = −.39, p = .006; this effect was similar across PTSD symptom categories, with significant correlations ranging from r = −.30 to r = −.44. However, only PTSD severity in the avoidance cluster was associated with less TPR recovery, r = −.29, p = .047. Total PTSD severity was associated with greater threat appraisal, r = .30, p = .035, and greater threat appraisal was associated with less CO recovery, r = −.33, p = .019. Results partially support the theory that greater PTSD severity and cognitive appraisals of threat contribute to less cardiovascular recovery when confronted with a stress‐inducing situation.